Rightsizing inventory - Aiello, Joseph L (Series on resource management, 2008)
Discusses how the entire internal and external supply chain of contributes to, or challenges, efforts to optimize product inventory and delivery. This book also discusses both obvious and hidden factors, including those related to sales, marketing, purchasing, manufacturing, warehousing, IT, and distribution